Guidance and Counseling Patterns in Developing Student Character in Madrasah - M Farid Yudha Bahari; Ayi Najmul Hidayat; Teti Ratnawulan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This article explores the patterns of guidance and counseling in developing student character within Madrasah settings. It emphasizes the importance of instilling strong character values in students, which are essential for their spiritual, social, and personal development. The study highlights that education is a conscious effort to create a learning atmosphere where students can actively develop their potential, including spiritual strength, self-control, personality, intelligence, and moral integrity. In conclusion, the article underscores the necessity of a comprehensive approach to character education in Madrasah, integrating religious, social, and environmental values to cultivate well-rounded individuals capable of contributing positively to society.